2015
DOI: 10.1111/gcb.13010
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and isoprene emission from trees along an urban–rural gradient in Texas

Abstract: Isoprene emission is an important mechanism for improving the thermotolerance of plant photosystems as temperatures increase. In this study, we measured photosynthesis and isoprene emission in trees along an urban-rural gradient that serves as a proxy for climate change, to understand daily and seasonal responses to changes in temperature and other environmental variables. Leaf-level gas exchange and basal isoprene emission of post oak (Quercus stellata) and sweet gum (Liquidambar styraciflua) were recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…However, these studies have often provided conflicting results. While some evidence suggested that g s increased with increasing temperature (Schulze et al , 1974; Lu et al , 2000; Mott and Peak, 2010), other studies found that temperature had no effect on stomata (Teskey et al , 1986; Sage and Sharkey, 1987; Cerasoli et al , 2014; von Caemmerer and Evans, 2015), or that increased temperature triggered stomatal closure (Weston and Bauerle, 2007; Lahr et al , 2015). One explanation for the conflicting results across these studies might be that the experiments were often conducted in uncontrolled environmental conditions in the field.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these studies have often provided conflicting results. While some evidence suggested that g s increased with increasing temperature (Schulze et al , 1974; Lu et al , 2000; Mott and Peak, 2010), other studies found that temperature had no effect on stomata (Teskey et al , 1986; Sage and Sharkey, 1987; Cerasoli et al , 2014; von Caemmerer and Evans, 2015), or that increased temperature triggered stomatal closure (Weston and Bauerle, 2007; Lahr et al , 2015). One explanation for the conflicting results across these studies might be that the experiments were often conducted in uncontrolled environmental conditions in the field.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported a complete range of responses to increased temperature, including stomatal opening (Schulze et al , 1974; Freeden and Sage, 1999; Lu et al , 2000; Mott and Peak, 2010), no significant response (Teskey et al , 1986; Sage and Sharkey, 1987; Cerasoli et al , 2014; von Caemmerer and Evans, 2015), and stomatal closure (Raven et al , 2005; Weston and Bauerle, 2007; Lahr et al , 2015). A peaked response with maximum g s at 20°C (Way et al , 2011) or more complex responses with one peak between 20 and 30°C and an additional increase at extremely high temperatures (Slot et al , 2016) have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…BVOC emissions are expected to rise with higher temperatures and decrease with elevated CO 2 (Lahr et al . ). The latter effect depends on nutrient availability.…”
Section: Tree Traits – a Moving Targetmentioning
confidence: 97%
“…7,8 Results of experiments that examined the direct dependence of stomatal conductance on temperature have not been consistent. Previous studies have reported a complete range of responses to increased temperature, including stomatal opening, [9][10][11][12] no significant response, [13][14][15][16] stomatal closure, [17][18][19] peaked response with maximum g s at temperatures optimal for photosynthesis 20 or more complex responses. 21 One possible explanation for these inconsistent results is that to isolate the direct effect of temperature on g s requires a well-controlled environment, particularly with respect to VPD, which is often hard to achieve.…”
Section: Textmentioning
confidence: 99%